Carl Priebe letter to Carl J. Bendorf regarding bird sightings in the fall 1990, September 28, 1990 - Priebe, Carlet al (1990)
Field reports with some sight detail submitted in a letter from Carl Priebe to Carl Bendorf for fall 1990. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1990. Epson - sheet feed